Keanekaragaman Kepiting pada Dead Coral (Pocillopora sp. dan Acropora sp.) Berdasarkan Perbedaan Kedalaman Di Perairan Teluk Pemuteran, Buleleng, Bali - I Gede Budi Astrawan; Elok Faiqoh; I Gusti Bagus Sila Dharma (Journal of Marine and Aquatic Sciences, 2021)
The Indonesian archipelago is a region with high marine diversity, especially in the coral reef ecosystem. Coral reefs have ecological functions such as habitat and foraging. However, coral reefs facing various threats including land pollution, fishing effects, climate change, and coral reef depletion caused by ocean acidity. The condition of coral reefs in Pemuteran waters now is much different from a few years ago. Many organisms symbiosis in living and dead corals, especially crabs. Water depth can affect the abundance of crabs. This study was to determine the level of crab diversity on dead corals (Acropora sp. And Pocillopora sp.) Based on differences in depth. The water depth was divided into 5 and 20 meters. Each depth is taken by three Acropora sp. and three Pocillopora sp. The types of crabs that obtained consist of the family Cheiragonidae, Eriphiidae, Leucosiidae, Majidae, Pilumnidae, Pinnotheridae, Porcellanidae, Xanthidae, Portunidae, and Goneplaciade. Highest composition of crab species in Acropora sp. depth of 5 meters 60% (Xanthidae) and depth of 20 meters 37% (Portunidae and Pilumnidae). Highest composition of crab species in Pocillopora sp. A depth of 5 meters 34% (Xanthidae) and depth of 20 meters by 37% (Pilumnidae). The highest density of Acropora sp. is 37.03 ind/cm2 and Pocillopora sp. is 229.63 ind / cm2. The diversity index analysis of crabs at 2 depths category is moderate, which means that the balance in the ecosystem is unstable, where there are some of species with low and high tolerance levels if there is a change in pressure from the environment.